Gondwana Link: connecting people, landscapes, and livelihoods across southwestern Australia - Bradby, K.; Keesing, A.; Wardell-Johnson, Grant (Blackwell Science Inc., 2016)
The Gondwana Link (GL) program spans some 1,000km and includes organizations, businesses, and individuals working to improve ecological function across the most intact large areas of habitat remaining in southwestern Australia (SWA). Noncompetitive leadership plus a focus on tangible achievement have been critical to providing the cohesion and initial momentum needed to support and inspire increased effort from those involved. Ongoing success rests on the responses of people working together, having respect for the integrity of the collective effort and for the specific roles of others across differing but complementary roles. Significant achievements have been secured, with progress in scientific knowledge generally following initial implementation of key actions. Lasting improvements in ecological health and resilience will only occur through larger-scale actions, which require more effort and time. The GL program has been an important initiative in strengthening the awareness of the distinctive ecological systems across SWA and the intertwined characteristics of resilience and fragility that characterize the region and its people. It has also had a role in inspiring and informing growth in large-scale connectivity programs nationally and internationally.